Pengaruh Ukuran Perusahaan, Komite Audit Dan Company Growth Terhadap Konservatisme Akuntansi (Studi Empiris Pada Perusahaan Teknologi yang terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Milda Tri Rahmawati; Adi Sofyana Latif (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research aims to analyze the relationship between company size, audit committee and company growth on accounting conservatism. Accounting conservatism is the principle of caution in disclosing financial statements, especially in expense and income post. This research uses a quantitative approach by connecting phenomena with relevant theories and hypotheses and is statistical in nature because the data used is in the form of numbers. The analytical method used is the associative method to determine the influence of the relationship between two or more variables. This research uses secondary data from Technology Companies listed on the Indonesia Stock Exchange in 2018-2022. Sampling for this research used purposive sampling, from a total population of 41 companies and there were 8 company samples with a total of 40 observation data. Secondary data collection techniques in this research are through documentation and literature study. The analysis technique used is descriptive statistical analysis and panel data regression because the data is cross section and time series using Eviews version 12. The research results show that simultaneously Company Size, Audit Committee and Company Growth influence Accounting Conservatism. And partially, company size (X1) has no effect on accounting conservatism, audit committee (X2) has no effect on accounting conservatism and company growth (X3) has a positive effect on accounting conservatism.